Agreement among optometrists and ophthalmologists in estimating limbal anterior chamber depth using the van Herick method. (12th February 2015) - Jindal, Anish; Myint, Joy; Edgar, David F.; Nolan, Winifred P.; Lawrenson, John G.
Abstract Purpose To evaluate the inter‐observer agreement for measuring limbal anterior chamber depth (LACD) using the van Herick test in community optometrists, glaucoma specialist optometrists and ophthalmologists. Methods The study was divided into two phases. In the first phase, a random sample of 100 UK community optometrists were given an opportunity to select and grade eight digital slit‐lamp images of anterior chamber angles using the original van Herick 4 point grading scale. The images were included in a clinical decision making study using computerised virtual case vignettes. In the second phase, hospital‐based glaucoma specialist optometrists and glaucoma sub‐specialist ophthalmologists graded the LACD of the right eye using a 7‐point % grading scale in 57 consecutively presenting patients with suspect glaucoma. Inter‐observer agreement was assessed using linearly weighted kappa (κw). Results Inter‐observer agreement for community optometrists was moderate, with a mean κw for grading photographic images of 0.50 (95% confidence interval (CI) 0.43–0.57). Overall, ninety‐two percent of observations were within one grade of the actual grade, although grading of narrow angles was associated with a 13% false negative error rate (based on a ≤ grade 2 threshold). For Phase 2 of the study, pairwise comparisons between optometrists and ophthalmologists showed that agreement was moderate to substantial (mean κw = 0.54–0.65) with a false negative rate of 1.9% (based on a ≤ 25% threshold). Grading accuracy of specialist optometrists and ophthalmologists were equivalent. Conclusions In summary, the present study found that community optometrists showed moderate inter‐observer agreement for grading LACD. Glaucoma specialist optometrists showed moderate to substantial agreement with weighted kappa values that were equivalent to sub‐specialist ophthalmologists. The augmented 7‐point % grading scale is intuitive and potentially offers greater accuracy for grading narrow angles than the traditional 4‐point scale for grading LACD.